Pelatihan Model Discovery Learning Untuk Meningkatkan Kemampuan Guru Menyusun Kisi dan Soal Hots - Yuastutik, Ida (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2022)
This school action study aims to improve teacher skills in compiling grids and questions at level 3 (based on HOTS). The results of the analysis of academic supervision in 2019 showed that 60% of the teachers in the cluster did not understand well the grid arrangement and level 3 questions to solve problems at school through training with the discovery learning model to be able to manage grids and questions. The research design is School Action Research (PTS). Increased teacher activity in observing the six stages of discovery learning, namely: a) Stage 1 Stimulation; b) Phase 2 Problem Formulation 3 Data Collection; d) Data Processing Stage 4 e) Stage 5 Verification; and f) Stage 6 Generalization. As a result, teacher training activities have increased from cycle I to cycle II as much as 11.34 (11.34%), for the cognitive aspect of teachers who got an A grade as many as 6 teachers (25%), class B as many as 15 teachers (62.5% ), and class C as many as 3 teachers (12,5%). The conclusion is that the use of the Discovery Learning model training can improve teacher training activities and skills in compiling grids and level 3 questions (HOTS) independently.